ANALISIS KEDUDUKAN HUKUM ISLAM DALAM SISTEM HUKUM DI INDONESIA - Baharuddin, Matta (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2012)
The legal status of Islam in Indonesia is equivalent to the Dutch East Indies heritage law and customary law. Indonesias population are Muslim, Islamic law is the source of the development of national law. Islamic law will be determined at the discretion of the national law as the legal government policy. Politicians, Muslim intellectuals and practitioners of Islamic law so to have a role in the enforcement of Islamic law into national law.